DESIGN OF AN EXPERT SYSTEM FOR IDENTIFICATION OF SHALLOT DISEASES USING BAYES THEOREM METHOD - Michael Sitorus (Jurnal Ilmiah Universitas Satya Negara Indonesia, 2023)
Disease is one of the risks that must be experienced by onion farmers. Disease on the red onion gives a lot of harm to farmers. Therefore it is very necessary tool to diagnose onion disease. Systematics is a good way to deal with this problem. The developed application is an expert system used to diagnose onion disease using Bayes Theorem Method. Data on onion diseases can be from the Agricultural Extension Agency located in Suko Village, Maron District, Probolinggo District. Diagnosis can be done by choosing the symptoms that are already available. Each symptom has a density to the disease which is then calculated using the calculation method. This program is created using C# (C-Sharp) language in Microsoft Visual Studio 2008 with MySQL software database. The disease-resistant application is fast and can deliver results. Results of disease diagnosis. Dental disease, treatment, countermeasures and level of trust are the computations of the Bayes Theorem Method.